Case of IV Stage Juvenile Nasopharyngeal Angiofibroma Presurgically Treated with a Single ECA Stop-Flow Embolization Technique Using Onyx 18 - Eliodoro Faiella; Domiziana Santucci; Davide Fior; Federica Riva; Chiara Tagliaferri; Laura Demelas; Giovanni D’ Aniello; Rosa Maria Muraca; Maurizio Bignami; Lorenzo Paolo Moramarco (Case Reports in Otolaryngology)
Background. Juvenile nasopharyngeal angiofibroma (JNA) is a rare tumor that mainly affects young boys. Its intervention may be complex due to its high vascularity, location, and extension. Preoperative embolization is used to prevent intrasurgical and postsurgical bleeding. Two main kinds of embolization are described in literature: intratumoral and transarterial, and numerous embolic materials are used. Case Presentation. We want to present a case of presurgical embolization of a stage IV JNA, performed using a single stop-flow balloon assisted technique with the balloon cuffed exclusively in the external carotid artery and using Onyx 18 as an embolic agent. Conclusions. The embolization with an exclusive external carotid artery single stop-flow technique using Onyx 18 is a safe, effective, and a definitive approach.